Culture if spikes? Indications and yield of blood cultures in hospitalized medical patients. Issue 5 (13th January 2016) - Linsenmeyer, Katherine; Gupta, Kalpana; Strymish, Judith M.; Dhanani, Muhammad; Brecher, Stephen M.; Breu, Anthony C.
Abstract : BACKGROUND: Although optimal utilization of blood cultures has been studied in populations, including emergency room and intensive care patients, less is known about the use of blood cultures in populations consisting exclusively of patients on a medical service. OBJECTIVE: To identify the physician‐selected indication and yield of blood cultures ordered after hospitalization to an acute medical service and to identify populations in which blood cultures may not be necessary. DESIGN, SETTING, AND PATIENTS: A prospective cohort study was performed at a single Veterans Affairs Medical Center from October 1, 2014 through April 15, 2015. Participants included all hospitalized patients on a medical service for whom a blood culture was ordered. MEASUREMENTS: The main outcomes were the rate of true positive blood cultures and the predictors of true positive cultures. RESULTS: The true positive rate was 3.6% per order. The most common physician‐selected indications were fever and leukocytosis, neither of which alone was highly predictive of true positive blood cultures. The only indication significantly associated with a true positive blood culture was "follow‐up previous positive" (likelihood ratio [LR]+ 3.4, 95% confidence interval [CI]: 1.8‐6.5). The only clinical predictors were a working diagnosis of bacteremia/endocarditis (LR+ 3.7, 95% CI: 2.5‐5.7) and absence of antibiotic exposure within 72 hours of the culture (LR+ 2.4, 95% CI: 1.2‐4.9). CONCLUSIONS: The rate of true positive blood cultures among patients on a medical service was lower than previously studied. Using objective and easily obtainable clinical characteristics, including antibiotic exposure and working diagnosis, may improve the likelihood of true positive blood cultures. Journal of Hospital Medicine 2016;11:336–340. © 2016 Society of Hospital Medicine